A phase 1b/2 clinical study of marstacimab, targeting human tissue factor pathway inhibitor, in haemophilia. (23rd August 2022) - Mahlangu, Johnny N.; Lamas, Jose Luis; Morales, Juan Cristobal; Malan, Daniel R.; Šalek, Silva Zupančić; Wang, Michael; Boggio, Lisa N.; Hegemann, Inga; Mital, Andrzej; Cardinal, Matthew; Zhu, Tong; Sun, Pengling; et al.
Summary: A phase 1b/2, three‐month study of marstacimab, a human monoclonal antibody targeting tissue factor pathway inhibitor (TFPI), was conducted in participants with haemophilia A or B, with or without inhibitors. Participants assigned to four cohorts received escalating weekly doses based on inhibitor status (without inhibitors: 300 mg, a single 300‐mg loading dose with subsequent 150‐mg doses, or 450 mg; with inhibitors: 300 mg). Safety outcomes were treatment‐emergent adverse events (TEAEs), injection site reactions, clinical and laboratory parameter changes. Efficacy was assessed by annualised bleeding rates (ABRs). Pharmacokinetics and pharmacodynamics (PD) were also evaluated. Among 26 treated participants [haemophilia A without inhibitor, n = 16 (61.5%); haemophilia A with inhibitor, n = 7 (26.9%); haemophilia B, n = 3 (11.5%)], 24 completed the study. Overall, 80.8% experienced TEAEs. ABR during treatment was significantly reduced versus an external on‐demand control group ( p < 0.0001) and versus pretreatment ABR ( p < 0.0001), with significant reductions observed across all dose cohorts. Marstacimab exposure generally increased in a dose‐related manner, with steady‐state concentration reached by day 57. Changes in pharmacodynamic biomarkers occurred across all dose cohorts. Marstacimab was safe and well tolerated. Clinically meaningful reductions in ABR and treatment‐related changes for all PD biomarkers indicated effective targeting of TFPI. (Clinicaltrials.gov identifier, NCT02974855).